Healthcare-associated infections and compliance of hand hygiene among healthcare workers in a tertiary health facility, southwest Nigeria. Issue 6 (November 2019) - Irek, Emmanuel O; Aliyu, Alhaji A; Dahiru, Tukur; Obadare, Temitope O; Aboderin, Aaron O
Introduction: Healthcare-associated infections (HAIs) are threats in healthcare settings contributing to increased morbidity, mortality and antimicrobial resistance worldwide. Hand hygiene (HH) is the simplest and most important single intervention to reduce HAIs. Aims/objectives: This study sought to determine rates of HAIs as well as compliance of HH among healthcare workers (HCWs) in Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC). Methods: A cross-sectional study was conducted among 227 HCWs (59 doctors, 129 nurses and 39 ward attendants) selected by multistage sampling across 10 hospital wards. Electronic interviewer-administered questionnaire, HH compliance checklist and point prevalence of HAI were done using World Health Organization and Centers for Disease Control and Prevention toolkits, respectively. Results: Only 20.33% (n = 12) of doctors, 3.88% (n = 5) of nurses and 2.56% (n = 1) of ward attendants had good knowledge of HH (χ 2 = 22.22, P value = 0.01). Among doctors, 11.86% (n = 7), 6.98% (n = 9) of nurses and 2.56% (n = 1) of ward attendants had positive perception towards HH (χ 2 = 7.87, P value = 0.25). Of the 174 opportunities for HH observed, compliance rates were 42.37%, 55.81% and 68.97% among doctors, nurses and ward attendants, respectively. Point prevalence of HAI was 16.38%. Discussion: Good knowledge and positive perception about HH were uncommon among doctors, nurses and ward attendants. However, ward attendants had the highest compliance to HH. There was a high prevalence of HAIs in this institution.